2010
DOI: 10.4314/wajm.v28i5.55005
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial and Community Acquired Infections in Korle Bu Teaching Hospital, Accra

Abstract: BACKGROUND: Nosocomial or hospital acquired infection has been recognized as a serious public health problem in the last twenty years. In most hospitals in Africa-South of the Sahara, although the types of community acquired infections are known, neither the magnitude, nor the common types of nosocomial infections has been documented. OBJECTIVE: This study was carried out to find the prevalence of hospital and community acquired infections in hospitals, and to estimate the overall prevalence of HAI and CAI in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 17 publications
(19 reference statements)
3
17
2
Order By: Relevance
“…This rate is higher than what is reported in developed countries with rates of 5–10% (Meers et al , 1980; Moro et al , 1986; Mayon-White et al , 1988; Scheel & Stormark, 1999) and also higher than rates reported from hospitals in developing countries such as Ghana (Newman, 2009) with 6.7% and Ethiopia (Gedebou, 1988) with 17%. There is need to strengthen infection control activities in Nigerian hospitals in order reduce the prevalence, mortality, morbidity, and cost of care associated with HAI.…”
Section: Discussioncontrasting
confidence: 57%
“…This rate is higher than what is reported in developed countries with rates of 5–10% (Meers et al , 1980; Moro et al , 1986; Mayon-White et al , 1988; Scheel & Stormark, 1999) and also higher than rates reported from hospitals in developing countries such as Ghana (Newman, 2009) with 6.7% and Ethiopia (Gedebou, 1988) with 17%. There is need to strengthen infection control activities in Nigerian hospitals in order reduce the prevalence, mortality, morbidity, and cost of care associated with HAI.…”
Section: Discussioncontrasting
confidence: 57%
“…The obstetrics unit accounted for the highest use of metronidazole (50.5%, n = 54) and amoxicillin-clavulanic acid (58.5%, n = 48) respectively. Figure 2 compares the top five antibiotic prescriptions at KBTH in 2000 [ 17 ] and 2017. In 2000, the most common antimicrobial in use at KBTH was metronidazole 212(44%), followed by ampicillin/amoxicillin 199(41.6%), gentamicin 168(34%) and cloxacillin 135(28%).…”
Section: Resultsmentioning
confidence: 99%
“…2 Top five antibiotic use in 2000 and 2017 at KBTH. Figures on antibiotic use in 2000 based on data by Newman, 2009 [ 17 ] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospitals serve a reservoir of various types of microorganisms; some may be multiple resistant to antibiotics [8] and the selective pressure of antimicrobial use in hospitals, therefore makes the environment a repository for these resistant strains [9]. Newman and his colleagues reported on the occurrence of nosocomial infections in Korle-Bu Teaching Hospital in Accra, Ghana [10]. These studies are therefore necessary and need to be conducted in many other parts of the country in order to generate national data on these pathogenic organisms, more especially on their antibiotic resistant patterns in Ghana.…”
Section: Introductionmentioning
confidence: 99%